2015
DOI: 10.1136/bcr-2014-207441
|View full text |Cite
|
Sign up to set email alerts
|

The unmasking of a pyopericardium

Abstract: Pyopericardium is a rare condition with a high mortality rate in which infection propagates in the pericardial space, leading to a pus filled pericardial effusion and cardiac tamponade, which can cause cardiogenic shock and death. We present a case of a previously healthy woman of 52, who was admitted with a severe lower respiratory tract infection that eventually led to a pyopericardium. The diagnosis of pyopericardium was delayed due to masking of symptoms by her underlying infection, sepsis and an upper gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Immunosuppression, alcohol abuse and previous pericardial inflammation can cause pyopericardium 4. In our case, the patient was an elderly man with diabetes mellitus and history of heavy smoking.…”
Section: Discussionmentioning
confidence: 73%
“…Immunosuppression, alcohol abuse and previous pericardial inflammation can cause pyopericardium 4. In our case, the patient was an elderly man with diabetes mellitus and history of heavy smoking.…”
Section: Discussionmentioning
confidence: 73%
“…Pyopericardium, or purulent pericarditis, is rare and rapidly fatal if left untreated. In treated patients, it has a mortality rate of up to 40%, related to cardiac tamponade and constriction 8–11 13–17. Pyopericardium can be caused by contiguous dissemination from pneumonia or empyema, by haematogenous spread, during cardiac or thoracic surgery or trauma 11 13 14.…”
Section: Discussionmentioning
confidence: 99%
“…Pyo-pneumopericardium is a rare medical condition where an infection propagates in the pericardial sac, leading to a pus-filled pericardial effusion and cardiac tamponade, that can cause cardiogenic shock and even death. [ 1 2 3 ] It is diagnosed when pus is drained directly from the pericardial space or when bacteria or fungi are cultured from the pericardial fluid. The majority of the reported cases are due to direct spread from pneumonia or empyema, however thoracic surgery, direct hematogenous spread and trauma can also cause the same.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) or magnetic resonant imaging (MRI) may aid the diagnosis as they can simultaneously show anatomical abnormalities of lung and mediastinal structures with better soft-tissue contrast and larger field of vision than a 2D-Echo. [ 1 9 10 ] Literature review demonstrated that Hemophilus influenza, Staphylococcus aureus , Viridans streptococci, Streptococcus pneumoniae and anaerobic bacteria to be the most common causative agent. However, few reports showed that gram-negative bacteria and fungi to be more frequent in immunocompromised hosts while others showed gram-positive coccis as the most commonly isolated organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation